Middle age a romance - Oates, Joyce Carol (New York Ecco, 2001)
The heroic death of sculptor Adam Berendt causes everyone who knew him in the affluent suburb of Salthill-on-Hudson to reevaluate their lives.
Prologue: Fourth of July -- If You Catch Me ... -- Survived by ... -- Old Mill Way: The Cave -- The Madonna of the Rocks -- The Game -- Farewell! -- ... And I Don't Escape You -- The Fell of Dark -- Old Mill Way: The Transformation -- The Girl in the Red Beret -- Deardeaddad -- The Missing -- Ever After -- Dream Creatures -- Old Mill Way: The Attack -- The Ballet -- The Lovers, by Night -- The Homecoming.
111782
Keywords: 2000-2099; Middle age -- Fiction; Death -- Fiction; Sculptors -- Fiction; Rich people -- Fiction; American fiction -- 21st century; Love -- Fiction; Love stories; Romance fiction; Fiction